2021
DOI: 10.18332/tpc/133019
|View full text |Cite
|
Sign up to set email alerts
|

Program uptake of a parent-tailored telephone smoking cessation counselling: An examination of recruitment approaches

Abstract: INTRODUCTION Recently, a Dutch proactive parent-tailored telephone smoking cessation counselling program, Smoke-free Parents (SFP), was demonstrated to be effective in helping parents to quit smoking. This study aimed to examine the program's uptake and the costs of two recruitment approaches (i.e. healthcare vs mass media) for SFP. In addition, parent's barriers to participating in SFP and the characteristics of participating parents were assessed. METHODS As part of an effectiveness-implementation hybrid tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…After reviewing the full text, 2848 studies were excluded with 135 remaining. Premised on inclusion and exclusion criteria, 101 of studies were excluded, and finally, 34 studies were included in our study 28–61 . The research flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full text, 2848 studies were excluded with 135 remaining. Premised on inclusion and exclusion criteria, 101 of studies were excluded, and finally, 34 studies were included in our study 28–61 . The research flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Premised on inclusion and exclusion criteria, 101 of studies were excluded, and finally, 34 studies were included in our study. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 The research flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…During this brief (5-10 min), free, informative, and proactive phone call, counselors provided more information about SFP (e.g., the costs of the program (between € 300 and € 370) that parents might need to pay if their health insurance did not reimburse the costs). Parents could withdraw or confirm their registration for SFP during this phone call (please see Scheffersvan Schayck et al [2021] [28] for more information and results on the implementation of the second step of the SFP referral tool).…”
Section: The Development Of An Implementation Strategy For Sfp In Child Healthcare Settingsmentioning
confidence: 99%
“…An effectiveness-implementation hybrid design is one that takes a dual focus a priori in assessing clinical effectiveness and implementation of, in this case the Dutch proactive telephone smoking cessation counseling SFP tailored to parents of children aged 0-18 years. The clinical effectiveness and program uptake among parents are published elsewhere [22,28]. The large trial was registered in the Netherlands Trial Register (NTR6092; registration date: 19/09/2016).…”
Section: Design and Ethicsmentioning
confidence: 99%